2016
DOI: 10.1016/j.fertnstert.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian hormone and pregnancy loss from the Effects of Aspirin in Gestation and Reproduction trial

Abstract: Objective To evaluate if anti-Müllerian hormone (AMH) is associated with pregnancy loss. Design A prospective cohort study within a block-randomized, double-blind, placebo-controlled trial of low dose aspirin. Setting Four U.S.A. clinical sites (2006-2012). Patients Women (n=1228) were aged 18-40 years with a history of one to two pregnancy losses and were actively attempting pregnancy without fertility treatment. Interventions None. Main Outcome Measures Pregnancy loss. Results Relative risks (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…In contrast, two other studies have suggested AMH is not associated with a higher rate of miscarriage (1921). A secondary analysis of the EAGER trial, which included women with at least one prior pregnancy loss attempting to conceive naturally, suggested women with a low AMH value (<1ng/mL) did not have an increased risk of pregnancy loss (19). Thus, it possible, that AMH is not a predictor of recurrent pregnancy loss, as suggested by Zarek at al ., but may play a role in spontaneous loss, as suggested by our cohort.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, two other studies have suggested AMH is not associated with a higher rate of miscarriage (1921). A secondary analysis of the EAGER trial, which included women with at least one prior pregnancy loss attempting to conceive naturally, suggested women with a low AMH value (<1ng/mL) did not have an increased risk of pregnancy loss (19). Thus, it possible, that AMH is not a predictor of recurrent pregnancy loss, as suggested by Zarek at al ., but may play a role in spontaneous loss, as suggested by our cohort.…”
Section: Discussionmentioning
confidence: 67%
“…Prior studies to date have failed to show such an association. 25,26 Second, not all women remained in the study for 12 cycles of attempt. This was anticipated, given the older reproductive-age cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we defined pregnancy loss dichotomously (no loss, at least 1). Cutpoints for gestational age of pregnancy loss(es) were based on the assumed development stage of the conceptus given the time of pregnancy loss recognition, with losses before 6 weeks representing pre-embryologic losses, 6 to 9 weeks representing embryo losses, and ≥10 weeks representing fetal losses [18,19]. Losses before 6 weeks are alternatively defined as “early pregnancy loss” and can represent pre-clinical pregnancy losses [2,20].…”
Section: Methodsmentioning
confidence: 99%